2007
DOI: 10.1007/s00299-007-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-deficit stress on the transcriptomes of developing immature ear and tassel in maize

Abstract: Water-deficit stress during meiosis is one of the most serious threats to crop production. To elucidate the mechanisms of the response to water-deficit stress in the reproductive organs of maize, we have characterized the changes in transcription that occur during meiosis in the tassels and floret formation in the ears following water deficit stress. We used oligo microarray analysis, which included 57,452 transcripts representing more than 30,000 identifiable unique maize genes, and combined this with reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…The pattern observed for starch and Suc metabolism-associated genes in drought-stressed ovaries suggests such an influence of the SnRK1 complex. The responses reported here that are related to raffinose and trehalose metabolism-associated genes were also reported by Zhuang et al (2007) for drought-stressed ear and tassels that were undergoing meiosis. This suggests that these stress responses, at least, are not specific to fertilized ovaries but also occur at earlier stages.…”
Section: Stress Responses In Raffinose and Trehalose Metabolismsupporting
confidence: 80%
See 2 more Smart Citations
“…The pattern observed for starch and Suc metabolism-associated genes in drought-stressed ovaries suggests such an influence of the SnRK1 complex. The responses reported here that are related to raffinose and trehalose metabolism-associated genes were also reported by Zhuang et al (2007) for drought-stressed ear and tassels that were undergoing meiosis. This suggests that these stress responses, at least, are not specific to fertilized ovaries but also occur at earlier stages.…”
Section: Stress Responses In Raffinose and Trehalose Metabolismsupporting
confidence: 80%
“…A small complementary DNA (cDNA) microarray containing about 2,500 cDNAs from maize was used to monitor gene expression specifically in developing maize endosperm and placenta/pedicel tissues during water deficit and rewatering at 9 DAP (Yu and Setter, 2003), a time when endosperm and placental tissues could be clearly distinguished. A transcriptomic study of the effect of drought on maize ears and tassels undergoing meiosis revealed raffinose and trehalose-associated genes as well as other carbohydrate-related processes (Zhuang et al, 2007). Beyond these observations, little is understood about the chain of molecular events leading to early embryo abortion in drought-stressed maize, and virtually nothing is understood about crucial events occurring upon fertilization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory genes involve proteins whose roles are related to signaling and transcription factors (Shinozaki & Yamaguchi-Shinozaki, 2007). In general, all biological processes are affected by water deprivation; however plants under water stress are more susceptible to other stresses (Zhuang et al, 2007). Temperature is one of the factors that can enhance the effect of water stress on plants.…”
Section: Genetic Analysismentioning
confidence: 99%
“…The identification and characterization of genes involved in drought tolerance brings knowledge about the perception of the stress and how plants respond to this adverse condition. Concerning this, studies have been performed aiming to identify new sources of variability in different crops (Cramer et al, 2007;Micheletto et al, 2007;Poroyko et al, 2007;Zhuang et al, 2007). Drought is firstly detected by root tissues.…”
Section: Genetic Analysismentioning
confidence: 99%